O combate à desinformação estatística no estudo de tabelas e gráficos - Lopes, Giulia Ottoni de Melo (Universidade Federal de São Carlos, 2024)
This research highlights the importance of combating statistical misinformation as a means of contributing to the development of literacy through the study of tables and graphs. We present several studies conducted by the Group for the Study and Planning of Mathematics Lessons, which were based on the São Paulo State Curriculum in effect from 2012 to 2014. Since 2018, the Common National Curriculum Base (BNCC) has served as the documentary basis for Brazilian education, in alignment with the phenomena of fake news and statistical misinformation. In this research, we propose a teaching approach as a method to counter misinformation, specifically aimed at promoting statistical literacy through the reading and interpretation of data in tables and graphs. Based on qualitative research, we analyze the content of each task aligned with the skills outlined in the BNCC, guided by the theoretical and methodological framework of statistical literacy.
Combating statistical misinformation in the study of tables and graphs
Keywords: Proposta de Ensino; Educação Básica; Letramento Estatístico; Teaching Approach; Basic Education; Statistical Literacy; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM